Recovery of antibody production after HIV infection in 'common' variable hypogammaglobulinaemia. - Webster, A D (1989)
A patient with a history of at least 10 years 'common' variable hypogammaglobulinaemia seroconverted to HIV-1 and became hypergammaglobulinaemic. The HIV isolated from his blood did not polyclonally activate B cells from normal donors. The mechanism of the hypergammaglobulinaemia is discussed.